Modeling The Distribution of Wastewater and Determining Zone of Initial Dilution from Waste Discharge Into The Sea From Fuel Terminal Activities in Balikpapan Bay - Randi Andhika; Purwanto Purwanto; Fuad Muhammad (Scientific Contributions Oil and Gas, 2024)
Sea water quality in Balikpapan Bay is determined by two driving factors: river flow and sea tides. This study aimed to conduct predictive modeling of wastewater distribution from industrial activities with the potential for seawater pollution, specifically for fuel terminals in Balik Papan Bay. The data source used was primary data for the initial environmental baseline, which was taken from the results of the analysis of 1 liter sample each from the wastewater treatment outlet, outfall, and three points representing three sea areas receiving wastewater, and secondary data obtained from the Badan Informasi Geospatial (BIG) and ECWMF (European Center for Medium-Range Weather Forecasts). The tidal data obtained were analyzed using the least-squares method. The results of the wastewater distribution model showed that all parameters, including pH, TSS, BOD, COD, ammonia, fatty oil, salinity, TOC, and Total coliforms, met seawater quality standards both at high and low tide conditions in the West and East Monsoon based on Government Regulation No.22 of 2021 concerning the Implementation of Environmental Protection and Management Appendix VIII for ports